Let M1 = (Q1, Sigma, delta1, q1, F1) accept L1, and let Let M2 = (Q2, Sigma, delta2, q2, F2) accept L2 Then M = (Q1xQ2, Sigma, delta, (q1,q2), F1 x(Q2-F2)) accepts L1-L2 where delta(r1,r2,a) = (delta1(r1,a), delta2(r2,a))At this point you should give a few words of justification about why you think this new machine would accept L1-L2. If the mathematical notation is just way to much for you, just try to explain things in intuitively.
0 1 ->p {p,q} {p} q {r} {r} r {s} {} *s {s} {s}Here the star means we have an accept state